GE_GERICHTE P/14508/2020 vom 17. August 2020 - GE Cour de justice (2020)
VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION;ENFANT;CURATELLE;CALOMNIE;INDUCTION DE LA JUSTICE EN ERREUR | CP.219; CP.174; CP.304